Pengaruh Penggunaan Alat Peraga Manik-Manik pada Materi Pecahan terhadap Hasil Belajar Matematika Siswa Kelas VII SMP Negeri 7 Mimika - Subhanudin Subhanudin; Jumiati Allo Toding (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the effect of using beaded props on fraction material on the mathematics learning outcomes of seventh grade students of SMP Negeri 7 Mimika. The type of experimental research used is True Experimental Design in the form of Pretest - posttest control group design. The variables of this study consisted of independent variables, namely the effect of using beaded props and the dependent variable, namely the mathematics learning outcomes of seventh grade students of SMP Negeri 7 Mimika. The study population consisted of all seventh grade students of SMP Negeri 7 Mimika, totaling 246 students. Data collection techniques are by means of tests, observation and documentation. Instruments to measure learning outcomes using pre-test and post-test that has been known homogeneity and normality. In the experimental group, the average pre-test value was 71.90 and the post-test was 88.43. In the control group, the average pre-test value was 60.23 and the post-test was 77.17. The results of hypothesis testing show that the significance value of tcount> ttable (10.20> 1.67). From these results it can be concluded that the use of props beads on fraction material brings a positive influence on the learning outcomes of students in grade VII SMP Negeri 7 Mimika.